Application of Temperature Fall-Off Interpretation Method in Superheavy Oil or Oil Sand SAGD Process. (13th August 2022) - Liang, Guangyue; Xie, Qian; Liu, Shangqi
Abstract : SAGD technology has been successfully and widely applied in the development of superheavy oil and oil sand projects. Before normal SAGD process, some preheating ways are often needed to realize interwell hydraulic connection, and this means that determining reasonable SAGD conversion timing from the preheating stage is an essential precondition for good performance. Previous numerical simulations or qualitative analysis of temperature fall-off data are often adopted in the industry, but they have deficiencies in terms of dependent on static geological model or insufficient data utilization. Therefore, on the basis of the temperature and pressure monitoring process comparison in China's superheavy oil and Canada's oil sand projects, this paper proposed a temperature fall-off interpretation model to obtain thermal diffusivity and preheating radius at different measurement points along the horizontal section by combining an unsteady thermal conduction model under constant heating power of wellbores in the radial coordinate system and approximately unsteady thermal conduction model with constant wellbore temperature and Fourier's law of thermal conduction. Besides, the duration time, interpretation method, and application flow chart of temperature fall-off test were presented. Then, it was validated to successfully determine the timing of SAGD conversion from the preheating stage by an example combining with tracking numerical simulation, temperature inflection point analysis, and index analysis during the partial-SAGD and initial SAGD stages. The findings of this study can help determine the SAGD conversion timing from the preheating stage simpler and faster especially for the case of long horizontal well section deployed with more temperature measurement points.